Latino/a experiences of homelessness in California: Qualitative findings from the California Statewide Study of People Experiencing Homelessness (CASPEH) - Zena K. Coronado; Michael Duke; Madison Rodriguez; Lourdes Johanna Avelar Portillo; Dafna Erana Hernandez; Margot Kushel (PLoS ONE, 2026)
The number of Latino/a people experiencing homelessness in the United States is increasing due to increased housing costs, economic disruption from the COVID-19 pandemic, and increased homelessness among migrants. There is little known about the lived experiences of Latino/a individuals experiencing homelessness. We conducted qualitative interviews in English and Spanish with 84 participants who self-identified as Latino/a as part of a large mixed methods representative study of homelessness. We analyzed qualitative interview transcripts from the California Statewide Study of People Experiencing Homelessness (CASPEH) to elucidate factors contributing to increased risk of homelessness for the Latino/a population, the vulnerabilities Latino/a individuals face while navigating homelessness, and how these vulnerabilities influence access to housing and services. Latino/a participants reported numerous factors that precipitated their descent into homelessness and challenged their ability to access social services and other resources. These factors include: 1) limited familial and social support, 2) barriers to housing returns, and 3) job loss precipitating homelessness and ongoing barriers to employment. We defined housing returns as successfully regaining housing such that participants no longer met criteria for homelessness. This could be through renting their own room or apartment, moving in with family or friends long-term, or moving into subsidized housing or permanent supportive housing. Our findings highlight challenges impacting Latino/a adults experiencing homelessness in California and provide evidence for developing culturally centered and programmatic interventions to address homelessness among this population.